2021
DOI: 10.3390/jnt2010002
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of InP/ZnS as Potential Anti-Cancer Therapy: Quantum Dot Treatment Increases Apoptosis in HeLa Cells

Abstract: InP/ZnS quantum dots (QDs) are an emerging option in QD technologies for uses of fluorescent imaging as well as targeted drug and anticancer therapies based on their customizable properties. In this study we explored effects of InP/ZnS when treated with HeLa cervical cancer cells. We employed XTT viability assays, reactive oxygen species (ROS) analysis, and apoptosis analysis to better understand cytotoxicity extents at different concentrations of InP/ZnS. In addition, we compared the transcriptome profile fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Our preliminary analysis using RT-qPCR showed that low but significant levels of SRRM4 mRNA were expressed in HeLa S3 cells, and the transfection of SRRM4 ASO caused induced caspase3/7 expression. A recent study showed that InP/ZnS quantum dot treatment induced apoptosis, resulting in the downregulation of SRRM4 mRNA in HeLa cells, which prevented tumor growth [ 47 ]. Caspase activation caused by chemically-modified phosphorothioate ASO was previously reported, which correlates with the hepatotoxicity in vivo [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary analysis using RT-qPCR showed that low but significant levels of SRRM4 mRNA were expressed in HeLa S3 cells, and the transfection of SRRM4 ASO caused induced caspase3/7 expression. A recent study showed that InP/ZnS quantum dot treatment induced apoptosis, resulting in the downregulation of SRRM4 mRNA in HeLa cells, which prevented tumor growth [ 47 ]. Caspase activation caused by chemically-modified phosphorothioate ASO was previously reported, which correlates with the hepatotoxicity in vivo [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a slight increase in the cell population at the early and late apoptotic stages that correlated with the incubation time. The increase in the population at the early apoptotic stage could be explained by the presence of alterations in membrane asymmetry and pre-lytic DNA fragmentation (Davenport et al, 2021). It is wellknown that early apoptosis involves the activation of multiple signal cascades and can be measured by the presence of Phosphatidylserine (PS) in the outer leaflet of the plasma membrane (detected with annexin V); late apoptosis represents the fragmentation of DNA (Elmore, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…ML-1, CA77, and fibroblast cells were maintained in DMEM with 10% FBS, 5% penicillin, and 5% amphotericin. These cell lines were cultured in a CO 2 incubator with 95% O 2 and 5% CO 2 as previously described [ 55 , 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%